Prognostic value of high-sensitivity cardiac troponin I in heart failure patients with mid-range and reduced ejection fraction - Lokaj, Petr; Spinar, Jindrich; Spinarova, Lenka; Malek, Filip; Ludka, Ondrej; Krejci, Jan; Ostadal, Petr; Vondrakova, Dagmar; Labr, Karel; Spinarova, Monika; Pavkova Goldbergova, Monika; Miklikova, Marie; et al. (PloS one, 2021)
BACKGROUND: The identification of high-risk heart failure (HF) patients makes it possible to intensify their treatment. Our aim was to determine the prognostic value of a newly developed, high-sensitivity troponin I assay (Atellica®, Siemens Healthcare Diagnostics) for patients with HF with reduced ejection fraction (HFrEF; LVEF < 40%) and HF with mid-range EF (HFmrEF) (LVEF 40%-49%). METHODS AND RESULTS: A total of 520 patients with HFrEF and HFmrEF were enrolled in this study. Two-year all-cause mortality, heart transplantation, and/or left ventricular assist device implantation were defined as the primary endpoints (EP). A logistic regression analysis was used for the identification of predictors and development of multivariable models. The EP occurred in 14% of the patients, and these patients had higher NT-proBNP (1,950 vs. 518 ng/l; p < 0.001) and hs-cTnI (34 vs. 17 ng/l, p < 0.001) levels. C-statistics demonstrated that the optimal cut-off value for the hs-cTnI level was 17 ng/l (AUC 0.658, p < 0.001). Described by the AUC, the discriminatory power of the multivariable model (NYHA > II, NT-proBNP, hs-cTnI and urea) was 0.823 (p < 0.001). Including heart failure hospitalization as the component of the combined secondary endpoint leads to a diminished predictive power of increased hs-cTnI. CONCLUSION: hs-cTnI levels ≥ 17 ng/l represent an independent increased risk of an adverse prognosis for patients with HFrEF and HFmrEF. Determining a patient's hs-cTnI level adds prognostic value to NT-proBNP and clinical parameters.
Keywords: Heart Transplantation; Stroke Volume; Disease-Free Survival; Heart-Assist Devices; Male; Models, Cardiovascular; srdeční selhání; Survival Rate; následné studie; Aged; mužské pohlaví; senioři; tepový objem; natriuretický peptid typu B; modely kardiovaskulární; transplantace srdce; Follow-Up Studies; peptidové fragmenty; senioři nad 80 let; troponin I; lidé; ženské pohlaví; Heart Failure; Humans; Natriuretic Peptide, Brain; Troponin I; Aged, 80 and over; podpůrné srdeční systémy; Peptide Fragments; Female; lidé středního věku; přežití bez známek nemoci; míra přežití; Middle Aged